Spectral asynchrony as a measure of ecosystem response diversity - Mazzochini, Guilherme G.; Rowland, Lucy; Lira‐Martins, Demétrius; Barros, Fernanda de V.; Flores, Bernardo M.; Hirota, Marina; Pennington, R. Toby; Oliveira, Rafael S. (Global change biology, 2024)
Species diversity is crucial for promoting ecosystem resilience and stability. Species diversity promotes complementarity in resource use, resulting in a wider range of responses to adverse conditions. This enables populations of different species to fluctuate asynchronously, maintaining ecosystem functioning during extreme climatic events. However, incorporating such mechanisms into conservation decisions and ecosystem modelling requires scalable metrics that represent species diversity, which is currently lacking. To address this, we introduce spectral asynchrony, a metric that captures the spatial heterogeneity of species’ functional responses occurring in distinct pixels. Here, we use remote sensing datasets to investigate the relationship between spectral asynchrony and productivity responses of seasonally dry tropical forests (SDTF) to climatic fluctuations. Our findings reveal that spectral asynchrony is associated with increased resistance and recovery of SDTF productivity in following extreme drought years, as well as greater productivity stability over two decades. Furthermore, higher spectral asynchrony was associated with relatively wetter regions, suggesting that increasing aridity across SDTF could potentially reduce landscape heterogeneity and limit ecosystem resilience to increasing droughts in the future. Spectral asynchrony provides an easily measurable and monitorable metric for assessing ecosystem responses to global changes, reflecting and scaling‐up the effects of species diversity at the local level. Species diversity enhances ecosystem resilience by promoting asynchronous population responses during climatic fluctuations. Addressing the need for scalable metrics in conservation and ecosystem modelling, we introduce spectral asynchrony, a novel metric reflecting the spatial heterogeneity of species’ functional responses over time. Utilizing remote sensing, our study establishes the association between spectral asynchrony and enhanced resistance, recovery, and stability in seasonally dry tropical forests, offering a practical tool for assessing ecosystem responses to global changes.